The Mesolithic at the Danube’s Iron Gates: new radiocarbon dates and old stratigraphies - Alexandru Dinu; Andrei Soficaru; Doru Miritoiu (Documenta Praehistorica, 2007)
In this paper we present 31 new AMS radiocarbon dates from the Mesolithic Iron Gates sites. The new dates allowed for a total reconsideration of the chronological sequences, and offer new insights for a reinterpretation of both Upper Paleolithic-Mesolithic and Mesolithic-Neolithic developments in the region.